Cytogenetic Analysis of Peripheral Blood Lymphocytes of Workers Occupationally Exposed to Benzene in A Fuel Station in Erbil City- Iraq - Hidayat, Hazha J.; Ismael, Mohammed S.; Hasan, Hewa H. (Science Journal of University of Zakho, 2016)
The objective of the present study was to evaluate genotoxic effects in petrol station workers, who were previously exposed occupationally to benzene in comparison with a selected control group, through inhalation and skin contamination, by using the cytokinesis- blocked micronucleus (CBMN) and chromosomal aberration tests carried on  peripheral blood lymphocytes. The study included  (35) male petrol station worker and 25  control subjects. Metaphase chromosome preparations were analyzed, chromosome aberrations in peripheral blood lymphocytes, were examined. The results showed that the frequency of cell with aberrations in exposed workers was significantly higher (P≤0.01) than that of control subjects. Most chromosome aberration found in exposed group was acentric fragment, chromosome break, dicentric. Furtheremore, also the frequency of micronucle( MN) was highly significant in benzyne exposed groups as compared with control person  (P≤0.01). In conclusion significant excess of chromosomal aberrations in workers who exposed occupationally to benzene, where compare to the matched controls.
Keywords: Genotoxicity; Lymphocytes; Petrol station workers; Chromosomal aberrations